Primary Care Doctors' Role in Antenatal Detection and Management of Fetal Bilateral Pleural Effusions: A Report of 2 Cases - Chai Li Tay; Noor Afiqah Binti Abdul Wahab (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: Fetal pleural effusion is rarely seen in primary care setting. It is more commonly diagnosed among women with diabetes mellitus in pregnancy. Method: This report illustrates two patients with fetal bilateral pleural effusions, detected at 18-week and 24-week period of amenorrhea (POA) during routine antenatal scans by primary care doctors. Result: These two pregnancies were complicated with hydrops fetalis and resulted in fresh stillbirth and intra-uterine death. Conclusion: Primary healthcare providers play an important role in the early diagnosis of fetal congenital anomaly, counseling regarding the ultrasonography findings, neonatal outcome, and referral to obstetrician for further management and monitoring for maternal complications, such as polyhydramnios, preeclampsia, mirror syndrome, and depression as a result of hydrops fetalis